La contribución de Paulo Freire a la práctica y la educación crítica en enfermería - Miranda, Karla Corrêa Lima (2004)
The authors present some biographical data about Paulo Freire, his main works and his most important production, showing the fertility of his legacy. This article aims to discuss the articulation of some concepts used by Freire in nursing practice and education, offering reflections for turning professional practice more critical and creative on the basis of this Brazilian educator's ideas.